Exploring the Dynamics of Transit Times and Subsurface Mixing in a Small Agricultural Catchment. Issue 3 (26th March 2018) - Yang, Jie; Heidbüchel, Ingo; Musolff, Andreas; Reinstorf, Frido; Fleckenstein, Jan H.
Abstract: The analysis of transit/residence time distributions (TTDs and RTDs) provides important insights into the dynamics of stream‐water ages and subsurface mixing. These insights have significant implications for water quality. For a small agricultural catchment in central Germany, we use a 3D fully coupled surface‐subsurface hydrological model to simulate water flow and perform particle tracking to determine flow paths and transit times. The TTDs of discharge, RTDs of storage and fractional StorAge Selection (fSAS) functions are computed and analyzed on daily basis for a period of 10 years. Results show strong seasonal fluctuations of the median transit time of discharge and the median residence time, with the former being strongly related to the catchment wetness. Computed fSAS functions suggest systematic shifts of the discharge selection preference over four main periods: In the wet period, the youngest water in storage is preferentially selected, and this preference shifts gradually toward older ages of stored water when the catchment transitions into the drying, dry and wetting periods. These changes are driven by distinct shifts in the dominance of deeper flow paths and fast shallow flow paths. Changes in the shape of the fSAS functions can be captured by changes in the two parameters of the approximating Beta distributions, allowing the generation of continuous fSAS functions representing the general catchment behavior. These results improve our understanding of the seasonal dynamics of TTDs and fSAS functions for a complex real‐world catchment and are important for interpreting solute export to the stream in a spatially implicit manner. Key Points: Transit times of discharge strongly related to storage Strong seasonality in discharge selection preference Seasonally changing SAS functions are well captured by Beta distributions